2014
DOI: 10.1155/2014/468605
|View full text |Cite
|
Sign up to set email alerts
|

Association between Two Common Polymorphisms and Risk of Hepatocellular Carcinoma: Evidence from an Updated Meta-Analysis

Abstract: Background. Recent studies suggested that two common polymorphisms, miR-146a G>C and miR-196a2 C>T, may be associated with individual susceptibility to hepatocellular carcinoma (HCC). However, the results remain conflicting rather than conclusive. Object. The aim of this study was to assess the association between miR-146a G>C and miR-196a2 C>T polymorphisms and the risk of HCC. Methods. A meta-analysis of 17 studies (10938 cases and 11967 controls) was performed. Odds ratios and 95% confidence intervals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…[20] in their meta-analysis observed that the significant risk of CT/TT genotypes was more evident in breast cancer and lung cancer in the former study and in breast cancer, Chinese, and Indian populations in the later one. This SNP, in addition, was shown to impact the risk of digestive system cancers [90], esophageal cancer [91], gastric cancer [14,92,93], the overall survival of patients with advanced gastric cancer [94], HCC and liver cirrhosis [70,95,96], gallbladder cancer [97], breast cancer [88,98,99], lung cancer [15,43,[100][101][102][103], prostate cancer [104], and others [105,106], although not in all studied populations [107][108][109][110]. These differences might reflect the fact that different ethnic and environmental exposures may have modified the risk of cancer.…”
Section: Discussionmentioning
confidence: 97%
“…[20] in their meta-analysis observed that the significant risk of CT/TT genotypes was more evident in breast cancer and lung cancer in the former study and in breast cancer, Chinese, and Indian populations in the later one. This SNP, in addition, was shown to impact the risk of digestive system cancers [90], esophageal cancer [91], gastric cancer [14,92,93], the overall survival of patients with advanced gastric cancer [94], HCC and liver cirrhosis [70,95,96], gallbladder cancer [97], breast cancer [88,98,99], lung cancer [15,43,[100][101][102][103], prostate cancer [104], and others [105,106], although not in all studied populations [107][108][109][110]. These differences might reflect the fact that different ethnic and environmental exposures may have modified the risk of cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Several meta-analyses ( Wang et al, 2012 , Xu et al, 2013 , Liu et al, 2014 , Wang et al, 2014 , Peng et al, 2014 ) have systematically summarized the potential association of the two SNPs with susceptibility to HCC. Compared with these previous results, for miR-146a rs2910164, our results differ from the first meta paper published by Wang et al (2012) , in that they did not observe any significant association between miR-146a and HCC risk under any genetic model.…”
Section: Discussionmentioning
confidence: 99%
“…For miR-196a-2 rs11614913, Xu et al (2013) only showed the polymorphism as a risk for HCC in Caucasians, not in Asians. Later work by Wang et al (2014) found a risk for HCC by the miR-192a SNP to be present in both Caucasians and Asians. However, the latest meta-analysis by Peng et al (2014) failed to observe any association for this SNP.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the miR146a rs2910164 polymorphism has been widely examined in various types of cancers. In several studies, the GG genotype was found to be associated with an increased risk of cancer including breast cancer (14), hepatocellular carcinoma (15). On the contrary, it was reported that the rs2910164 CG or GG genotype was associated with a significantly decreased risk for lung cancer compared to that of the CC genotype (31).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it is also reported that miR146a rs2910164 can directly inhibit the expression of IRAK1 and IRAF6, impair nuclear factor (NF-ĸB) activity, and suppress several NF-ĸB targeted inflammatory genes, such as IL-6, IL-8, IL-Iβ, and TNF-α (6,8). The variant C allele at miR146a rs2910164 polymorphism was associated with an elevated risk of prostate cancer (12), breast cancer (13,14) and hepatocellular carcinoma (15). On the contrary, there is a meta-analysis report summarizing that the miR146a rs2910164 GG genotype, not CC or CG, was associated with increased gastric cancer risk (16) and breast cancer (17).…”
mentioning
confidence: 99%